Antibodies and Immunity During Kawasaki Disease - Hicar, Mark Daniel (Frontiers in Cardiovascular Medicine, 2020)
The cause of Kawasaki disease (KD), the leading cause of acquired heart disease in children, is currently unknown. Epidemiology studies support that an infectious disease is involved in at least starting the inflammatory cascade set off during KD. Clues from epidemiology support that humoral immunity can have a protective effect. However, the role of the immune system, particularly of B cells and antibodies, in pathogenesis of KD is still unclear. Intravenous immunoglobulin (IVIG) and other therapies targeted at modulating inflammation can prevent development of coronary aneurysms. A number of autoantibody responses have been reported in children with KD and antibodies have been generated from aneurysmal plasma cell infiltrates. Recent reports show that children with KD have similar plasmablast responses as other children with infectious diseases, further supporting an infectious starting point. As ongoing studies are attempting to identify the etiology of KD through study of antibody responses, we sought to review the role of humoral immunity in KD pathogenesis, treatment, and recovery.